Optical Coherence Tomographic Features and Prognostic Values of Macular Edema in Vogt-Koyanagi-Harada Disease - Qin, Peng; Ye, Zi; Su, Guannan; Kijlstra, Aize; Yang, Peizeng (Frontiers in Medicine, 2022)
Purpose: To determine optical coherence tomographic (OCT) features of macular edema (ME) and identify potential prognostic values for ME and visual outcomes in Vogt-Koyanagi-Harada disease (VKH). Methods: In the retrospective case series, a total of 1,377 VKH patients who were seen in a tertiary uveitis center between September 2011 and January 2018 were reviewed on their demographics, visual acuity, ocular and extraocular manifestations, modes of treatment, and OCT examinations. Of these patients, 79 having ME were included for analysis of OCT features. Four patients were missed without ME resolution, and the remaining 75 patients who either had ME resolved or were followed up for 2 years were included for analysis of disease outcomes. Results: Of the 115 affected eyes in these 79 patients, 100 (87.0%) had cystoid ME (CME), accounting for the most common OCT feature of VKH-related ME. Disruption of the inner-segment/outer-segment junction (IS/OS) band seen in 33 (28.7%) affected eyes of 24 (30.4%) patients was found as a risk factor for the development of persistent ME (10 of 62[16.1%] vs. 13 of 13[100%]; P<0.001) and a poor visual outcome (1.16+-0.42 vs. 1.17+-0.46 in logMAR unit; P=0.89). CME patients with a concurrent choroidal neovascular membrane often had a disrupted IS/OS band, thus becoming refractory cases. A 6-month well-controlled intraocular inflammation following standard treatment regimens was found to associate with complete resolution of the refractory edema (4 of 5[80%] vs. 2 of 13[15%]; P=0.02). Conclusions: Intraretinal cystoid changes are most commonly seen in the edematous macula of VKH patients. Disruption of the IS/OS band is a useful risk sign for poor ME and visual outcomes in VKH-related ME, and a long-term well-controlled intraocular inflammation may be critical for the resolution of refractory cases.